PENGARUH MODEL QUANTUM TEACHING TERHADAP MINAT BELAJAR ANAK USIA DINI DI RA AL HIDAYAH CITAPEN - Astarina Arif; Ibnu Imam Al Ayyubi; Murharyana; Hevie Setia Gunawan (Jurnal El-Audi, 2023)
Interest greatly influences the learning process because if learning activities are adjusted to the interests of the child, the child will learn as well as possible and the learning objectives will be achieved. The purpose of this research is to find out whether there is a relationship between the Quantum Teaching model and the learning interest of students at RA Al Hidayah. The formulation of the problem in this study is to find out whether the Quantum Teaching model can influence student learning interest at RA Al Hidayah an overview of students' interest in learning at RA Al Hidayah, as well as finding the right strategy to apply the Quantum Teaching model as a new model of learning in increasing student interest in learning at RA Al Hidayah. While the method used in this research is a single experimental design and uses data collection techniques through documentation, observation and checklist techniques. The data analysis technique used in this study is the Point Axceeding Median (PEM). Based on the results of the research activities carried out, as well as testing the results of the data obtained, the researchers concluded that the Quantum Teaching model method can significantly affect children's learning interest, this can be seen from the maximum PEM value of 100 and a positive Tau Value.